Da'wah or destruction? - Deedat, Ahmed ([Kuala Lumpur] : Saba Islamic Media, 2008)
Sheikh Ahmed Deedat talk on da'wah in Islamic aspects
Title from title screen
Lecturer: Sheikh Ahmed Deedat
DVD format
Keywords: Da'wah (Islam); Islam -- Missions